Technical and technological equipment of vegetable crops production in Russia - A. V. Soldatenko; N. D. Avarskii (Овощи России, 2025)
Relevance and Methods. The study is devoted to the analysis of the state of technical and technological support for the production of vegetable crops in Russia. During the research, the following methods were used: analytical, monographic, economic-statistical and expert assessment.Results. It provides data on self-sufficiency in vegetable production, production of vegetable crops in farms of all categories over the past 5 years, as well as changes in the cost of production and the cost of sales of these products. The issues of providing vegetable growing with agricultural machinery and equipment, the introduction of digitalization processes in the vegetable growing sub-sectors, as well as existing measures of its state support are considered. As a result of the analysis of the current state of technical and technological support for vegetable growing, as well as the existing state support for the production of vegetable crops, the main elements that need to be developed to increase the efficiency of this sub-branch of crop production have been identified.Conclusion. Vegetable growing is one of the most significant sub-sectors of crop production, ensuring consumer demand of the population and food security in Russia; in order to achieve the necessary level of self-sufficiency in vegetable production, appropriate technical and technological support for their producers is necessary; to solve this problem, it is necessary to introduce innovative technologies for the production of vegetable products, as well as to provide the necessary amount of modern high-performance machinery and equipment, which is possible only with effective state support for the technical and technological modernization of vegetable production.